ANALISIS PEMANFAATAN MODAL KERJA DALAM KEGIATAN OPERASIONAL PADA PT. PERKEBUNAN NUSANTARA III (PERSERO) MEDAN - Okky Anatasya Tarigan; Hotnida Sirait (Fakultas Ekonomi Universitas Methodist Indonesia, 2018)
The purpose of this study is to analyze the use of working capital in operational activities at PT. Perkebunan Nusantara III (Persero) Medan. Based on the results of the research through analysis of liquidity ratios measured by current ratio, quick ratio, cash ratio, and net working capital and activity ratio analysis as measured by receivable turnover, inventory turnover, working capital turnover, fixed asset turnover, and total assets turnover, the company has not been able to use the existing working capital due to fluctuations and corporate debt that exceeds its current assets.